2012
DOI: 10.1159/000338299
|View full text |Cite
|
Sign up to set email alerts
|

Evidence in Favor of a Severely Impaired Net Intestinal Calcium Absorption in Patients with (Early-Stage) Chronic Kidney Disease

Abstract: Introduction: Calcium and phosphorus are essential to many vital physiological processes. Little is known about the net and fractional intestinal absorption of calcium and phosphorus in patients with chronic kidney disease (CKD) and their clinical and hormonal determinants. Methods: Blood and 24-hour urine samples were collected in 20 healthy volunteers (HV) and 72 stable CKD stage 1–4 patients and analyzed for parameters of mineral metabolism including calcidiol, calcitriol, and parathyroid hormone (PTH). Die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…CKD is often associated with type 4 renal tubular acidosis, which in turn, is characterized by decreased renal ammoniagenesis and more acidic urine (21) that favors UA supersaturation (22). Furthermore, urinary calcium excretion is reduced among those with declining GFR, perhaps making calcium stones less likely (23). Obesity, insulin resistance, and diabetes, which are also more common with aging, are associated with lower urinary pH and UA stones (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…CKD is often associated with type 4 renal tubular acidosis, which in turn, is characterized by decreased renal ammoniagenesis and more acidic urine (21) that favors UA supersaturation (22). Furthermore, urinary calcium excretion is reduced among those with declining GFR, perhaps making calcium stones less likely (23). Obesity, insulin resistance, and diabetes, which are also more common with aging, are associated with lower urinary pH and UA stones (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the percentage of patients with UA stones increased with age. The UA increase could be associated with decreasing urine pH and increasing UA excretion [ 24 ] related to obesity, insulin resistance, and diabetes that are common with aging [ 10 24 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously suggested that calcium absorption may be severely impaired in early CKD based on very low observed urinary calcium excretion in these patients [21•]. However, evidence from calcium balance and kinetic studies illustrate that, despite very low urine calcium levels, patients with moderate (stage 3/4) CKD have fractional calcium absorption rates similar to healthy adults when dietary calcium is adequate [7•].…”
Section: Calcium Metabolismmentioning
confidence: 99%